Inhibitory effect of Polyram DF and Capsicum annum on leaf spot of rose caused by Curvularia lunata in vitro and in planta - Qaisar, Muhammad Hussnain; Rani, Hafiza Kashaf; Shaheen, Hafiz Muhammad Usama; Zafar, Hammad; Ahmed, Hadeed; Kachelo, Ghalib Ayaz; Rehman, Abdul; Atiq, Muhammad; Rajput, Nasir Ahmed (Plant Science Today, 2023)
Rose plants are affected by several diseases caused by fungi, nematode, bacteria, viruses, and other pests. Among all of these, Curvularia lunata causes significant losses to Roses. Present study was focused on In-vitro and In-vivo management of the “Curvularia leaf spot of Rose” caused by Curvularia lunata by using different fungicides and phyto-extracts. Diseased samples were collected from floriculture area of University of Agriculture, Faisalabad for isolation of pathogen. Five fungicides i.e., Cabrio-Top, Curzate-M, Aliette, Polyram-DF and Recado @ (50ppm, 100ppm and 150ppm) and five plant extracts i.e., Allium cepa, Capsicum annuum, Aloe vera, Menthaand Calotropis gigantean with three concentrations @ (5%, 10% and 15%) were evaluated under lab conditions through poisoned food technique by using Complete Randomized Design (CRD), where C. annuum gave best results (9.129mm) followed by Calotropis gigantea (13.003mm), and Polyram-DF was effective (2.218mm) followed by Curzate-M (6.542mm). Best performing fungicides and plant-extracts were subjected to In-vivo management trials. Under green-house conditions, combination of Capsicum annuum + Calotropis gigantean and Polyram-DF + Curzate-M were shown least disease incidence (14.517 and 3.224%). LSD was used for comparing variations between treatments at 5% probability. The results of these experiments were to aid in the evaluation of fungicides and Phyto-extracts, which are the most effective chemicals and phyto-extracts against leaf Spot disease of Rose.